“Cassia auriculata-derived silver nanoparticles as a novel male contraceptive agent” - Prity Yadav; Neha Bharti; Phulwanti Kumari Sharma; Pratap Chand Mali (Pharmacological Research - Modern Chinese Medicine)
Introduction: The development of male contraception remains a crucial area of research in reproductive health. Nanotechnology offers innovative solutions, with plant-derived nanoparticles emerging as potential antifertility agents. This study explores the antifertility effects of Cassia auriculata-derived silver nanoparticles (AgNPs) as a novel approach to male contraception. Cassia auriculata, a medicinal plant with known therapeutic properties, plants of the genus Cassia are used mainly in traditional Chinese medicine (TCM) to control type 2 diabetes, skin and wound healing, as a mild laxative, and for urinary tract health, with active constituents including 1-Tetradecanol, Anthraquinone, Emodin, Quercetin-3-glucoside, β-sitosterol, Rutin, β-sitosterol-β-D-glucoside, was utilized for the green synthesis of AgNPs, ensuring eco-friendliness and biocompatibility. Methods: The synthesized nanoparticles were characterized using UV-Vis spectroscopy, XRD (X-Ray diffraction), FTIR (Fourier Transform Infra-Red), DLS (Dynamic Light Scattering), Zeta Potential, and SEM (Scanning Electron Microscopy) to confirm their physicochemical properties. Results: In vivo studies on male albino rats revealed significant reductions in sperm density and motility, alongside alterations in testicular and epididymal histology, indicating impaired spermatogenesis. Hormonal analysis showed a decline in testosterone levels, further supporting the antifertility potential of these nanoparticles. Importantly, toxicity assessments confirmed minimal systemic side effects, highlighting their safety profile. Discussion: The findings suggest that Cassia auriculata-derived AgNPs could be a promising non-hormonal male contraceptive with reversible effects. This research underscores the potential of nanotechnology in reproductive health and paves the way for further clinical investigations into plant-based nanoparticle contraceptives.